Disparities in Persistent Victimization and Associated Internalizing Symptoms for Heterosexual Versus Sexual Minority Youth. (30th March 2019) - Kaufman, Tessa M. L.; Baams, Laura; Veenstra, René
Abstract : This study investigated whether lesbian, gay, and bisexual (LGB) adolescents were at higher risk for persistent victimization of bullying compared to heterosexual adolescents, and how victimization trajectories were associated with internalizing symptom development across LGB and heterosexual adolescents. Data came from a five‐wave study ( M age T1 = 11.1 to M age T5 = 22.3; n = 151 LGB; n = 1, 275 heterosexual) and informants were adolescents and their parents. Adolescents were classified in three victimization trajectories: persistent (5.6%), decreasing (28.1%) or low (66.3%) victimization. LGB adolescents reported more persistent victimization, relative to no (OR = 6.79, 95% CI [3.52, 13.13]) or decreasing victimization (OR = 3.09, 95% CI [1.53, 6.24]), compared to heterosexual peers. Further, persistent victimization was more strongly associated with anxiety among LGB than among heterosexual adolescents.